Elevated natural radionuclides in soils and stream sediments: pollution, spatial distribution, radiological hazards, and cancer risks in peri-urban Emure-Ekiti, southwest Nigeria - Olaniyi JohnPaul Popoola; Omodele Emmanuel Olubi; Oladimeji Samuel Adewalure; Augustine Enoch Raphael (Discover Soil)
Abstract This study examines natural radionuclide contamination and health risks in the soils and sediments of Emure-Ekiti, Southwest Nigeria. For this study, a total of 20 samples (10 soils and 10 stream sediments) were collected at a depth of 10 cm. 238U, 232Th and 40 K were analyzed in the samples using X-Ray Fluorescence (XRF) technique. The research shows that the soil has high levels of 23⁸U at 121.69 Bqkg−1 and 4⁰K at 1659.45 Bqkg−1, which are above global averages. In contrast, 232Th in the soil measured at 47.62 Bqkg−1 is slightly below what regional studies report, yet it still exceeds the global average. These findings are important because they highlight potential concerns regarding radiation. Additionally, the stream sediments indicate increased levels of 232Th at 59.34 Bqkg−1 and 4⁰K at 1531.98 Bqkg−1, further emphasizing the importance of monitoring these elements. The Radium Equivalent Activity (Raeq) values for both soils at 317.56 Bqkg−1 and sediments at 343.12 Bqkg−1 are close to or exceed the UNSCEAR safety limit of 370 Bqkg−1, signaling potential radiological hazards. This situation points to moderate contamination from uranium (U) and potassium (K), while thorium (Th) ranges from uncontaminated to moderately contaminated. Several radiological hazard indices, such as dose rates and exposure indices for internal and external environments, exceed safety limits. This highlights significant radiation risks, especially since soils have exposure rates reaching 1093.45 µR/h, indicating them as a major source of external radiation. Health risks are significant, with both external and internal hazard indices being above safety thresholds. The Annual Effective Dose Equivalent (AEDE) surpasses the global average, and cancer risks (ELCR) show moderate to high levels, particularly indoors. Specific health concerns include the potential for radiation-induced damage to the lungs, ovaries, testes, and bone marrow. To address these issues, the study recommends regular monitoring of radiation levels, improving ventilation in indoor spaces, educating the public on the risks of radiation, and providing safety guidelines for using local materials.